(untitled) (LACCEI, 2024)
This paper presents the design and performance analysis of a hybrid wind and solar energy generation system integrated with a battery bank for a building. The objective of this study is to evaluate the extent to which the energy demand of the building can be met by the hybrid system and to investigate the effects of various parameters on system performance. The hybrid system comprises nine wind turbines, a solar photovoltaic (PV) array, and a battery bank, all integrated with the building’s electrical grid. A simulation model is developed using Designbuilder/EnergyPlus to estimate the energy demand of the building. This model considers the building’s energy consumption, weather data, and the wind turbine and PV array characteristics. The simulation results show that the hybrid system can effectively cover a significant portion of the building’s energy demand. The battery bank plays a crucial role in ensuring a continuous electricity supply. The effects of various parameters, such as wind speed, solar irradiation, and battery capacity, on system performance, are also analyzed. The findings of this study can serve as a basis for the optimization of hybrid renewable energy systems for building applications, thereby contributing to the development of sustainable energy solutions.